METHOD FOR INCIDENT/POTENTIAL CRISES DETECTION - Карпінський, Микола Петрович; Корченко, Анна Олександрівна; Гізун, Андрій Іванович (Ukrainian Information Security Research Journal, 2015)
The information technology development with increasingdependence of human society from them is also thedanger of a sharp increase in information securityincidents in the absence of control over them can causecrises. The higher the level of incident/potential crisiscriticality causes the serious damage and it requires amuch more serious security. Major aspects thatdetermines the security effectiveness is the automation,timely detection and identification of incidents. In thispaper method of incidents/potential crisis identifyingbased on the application of fuzzy sets theory and expertapproaches was proposed. Thus the method can be usedin conditions of weakly-formalized environment, likeinformation and communication systems or networks.This method consists of 6 phases: forming sets ofincidents/potential crisis and identifying parameters;forming ties incident – identifying the set of fuzzyparameters; formation of standards fuzzy parameters;forming sets of heuristic rules for detection andidentification of incidents; phasing parameters monitoredto identify incident; processing parameters and formationresult. The proposed method can be used single or incombination with the method of assessing the criticalitylevel of the situation due to the influence of theincident/potential crisis.